Kajian Hadis: Historiografi Yahudi - Israel Dan Muslim - Palestina - Ali Mohtarom (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2022)
Jerusalem was built by the Arabs of the Right long before the Jews came to the city. It was built by Arab Jebus four thousand years BC, or 2100 years before the arrival of the Prophet Abraham, and 2,700 years before the arrival of the Prophet Moses who brought the teachings of the Torah which became the source of Jewish teachings. In history, after the Arab tribe of Yebus was built, Jerusalem was recorded to have been under the rule of Pharaoh, Jews for about 73 years, Babylonians, Persians, Greeks, Romans, Islamic rule I led by Umar bin Khattab in the 15th year Hijri, Christians, Islamic rule II by Salahuddin al-Ayyubi, then the Ottomans in 1615 until it fell to the British in 1917, and in 1948 the state of Israel was established. History records that relations between Muslims and Jews have always been filled with tension after tension. Of course, these tensions arose from the injustice of the Jews in many ways. Along with the Qur'an and hadith as well as historical facts as the main sources of information, this article informs us that the attitudes and views of the Jews towards Islam tend to be brutal.